Economic analysis of milk production in southern and North coastal regions of Andhra pradesh - N Naresha, Anil K. Dixit, Ajmer Singh and B.S. Meena (Indian Journal of Dairy Science, 2023)
A study on economic analysis of milk production has been carried out in Chittoor and Vishakhapatnam district of Andhra Pradesh. Using the cumulative square root frequency method, farms were divided into small, medium, and large groups based on the number of milch animals A predetermined sample of 80 dairy farmers were drawn randomly from selected four villages of Chittoor and Vishakhapatnam districts of Andhra Pradesh during 2019-20. The cost and return calculation was using the budgeting technique. Fixed costs and variable costs were both considered for estimation using the capital recovery cost technique. The overall maintenance cost per day per animal was highest for buffalo, followed by cross breed and indigenous cow. The overall cost of milk production was highest in case of indigenous (₹32.57/litre) cow followed by buffalo (₹31.12/litre) and cross breed (₹22.64/litre). Study reveals that Buffalo were found to be profitable than crossbreed and indigenous cows. Milk productivity is highest for crossbreed cows compared to indigenous cows and buffalos. Because of higher market price of milk for buffalo, overall net returns of buffalo are higher than crossbreed and indigenous cows.